15. Comparison of EMG activity during stable and unstable standing and sitting in patients with primary orthostatic tremor. Issue 3 (March 2016) - Tai, Yi-cheng; Ha, Ainhi D.; Yin, Katie; Chen, Shi; Mahant, Neil; Fung, Victor S.C.
Abstract : Background: Primary orthostatic tremor (OT) is characterised by 14–16 Hz leg and truncal tremor when standing, accompanied by an intense sense of unsteadiness. Both are relieved by sitting or walking. Methods: To evaluate whether OT pathogenesis is related to stance or isometric muscle contraction, and whether normal subjects develop OT when feeling unsteady, we recorded electromyographic (EMG) activity in leg and paraspinal muscles of 9 OT and 8 controls during 5 conditions: quiet standing; unsteady standing; supported standing; supported sitting; and unsupported sitting. A handheld potentiometer was used to indicate levels of subjective unsteadiness. Spectral analysis was used to quantify OTP (OT Power, mean EMG power between 13–18 Hz) and OTPR (ratio between OT power and mean EMG between 2–25 Hz). Results: OTP was significantly higher in patients compared with controls during quiet and unsteady standing. In patients, OTP was attentuated during supported standing without significant changes in OTPR. During unsupported sitting, 33% of patients developed typical OT EMG activity, 22% demonstrated poorly formed OT bursting and in the remaining 45% there was not tremor. No controls developed OT. Comparing supported standing with unsupported sitting in patients, OTP was similar during both, but OPTR was significantly higher during supported standing versus unsupported sitting, suggesting a disproportionate increase in mean non-tremor locked EMG during unsupported sitting. Conclusion: OT is primarily elicited by standing rather than isometric contraction. OTPR remains similar when the requirement of balance maintenance was alleviated. OT was seen in only some patients during non-standing posture maintenance requiring isometric contraction. Only one control developed poorly formed OT isolated to the leg muscles during Unsteady Standing, arguing against OT being a physiological response to unsteadiness.